2019
DOI: 10.1042/bsr20181635
|View full text |Cite|
|
Sign up to set email alerts
|

miR-26a prevents neural stem cells from apoptosis via β-catenin signaling pathway in cardiac arrest-induced brain damage

Abstract: Neural stem cells (NSCs) transplantation is one of the most promising strategies for the treatment of CA-induced brain damage. The transplanted NSCs could differentiate into new neuron and replace the damaged one. However, the poor survival of NSCs in severe hypoxic condition is the limiting step to make the best use of this kind of therapy. In the present study, we investigated whether the overexpression of miR-26a improves the survival of NSCs in hypoxic environment in vitro and in vivo. In vitro hypoxia inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Oxygen concentration may occur to be below 1% in the onset area of pathological hypoxic diseases, such as acute plateau edema, stroke and cerebral embolism, and brain tumors, and in even severe cases [52,53], anoxia may happen. According to early studies, 1% oxygen concentration significantly impeded the speed of proliferation and reduced the amount of NSCs [18], and the prolonged excessive hypoxia caused a considerable rise in NSC apoptosis and therefore could lead to irreversible damage to the nervous system [54,55]. Our studies revealed that prolonged hypoxic exposure could significantly induce apoptosis of NSCs and decrease the number of those cells.…”
Section: Discussionmentioning
confidence: 55%
“…Oxygen concentration may occur to be below 1% in the onset area of pathological hypoxic diseases, such as acute plateau edema, stroke and cerebral embolism, and brain tumors, and in even severe cases [52,53], anoxia may happen. According to early studies, 1% oxygen concentration significantly impeded the speed of proliferation and reduced the amount of NSCs [18], and the prolonged excessive hypoxia caused a considerable rise in NSC apoptosis and therefore could lead to irreversible damage to the nervous system [54,55]. Our studies revealed that prolonged hypoxic exposure could significantly induce apoptosis of NSCs and decrease the number of those cells.…”
Section: Discussionmentioning
confidence: 55%
“…cardiac arrest-induced brain damage by the activation of the β-catenin signaling pathway [32]. Moreover, we have found that the elevated miR-26a and restrained EZH2 could ameliorate the apoptosis of osteoblasts in SONFH by repressing Bax and elevating Bcl-2.…”
Section: Discussionmentioning
confidence: 80%
“…MiR-26a, a brain-enriched microRNA mainly localized within axonal compartments of neurons, has been hypothesized to play a key role in axon development and regeneration (41,42), and also involved in the formation, maturation and/or plasticity of synapses via regulating distinct sets of target genes (43). For example, it has been suggested that miR-26a is involved in regulating excitatory neurotransmission under stress condition (44), and maintains stress resiliency and antidepressant efficacy by targeting the serotonergic autoreceptor (33).…”
Section: Discussionmentioning
confidence: 99%